DIFFERENT DOSES OF RECOMBINANT FSH AND DETERMINING PARAMETERS OF OXIDATIVE STRESS - Tulic, Lidija; Tulic, Ivan; Stojnic, Jelena; Bila, Jovan; Vukovic, Zeljka; Kotlica, Boba (Journal of Medical Biochemistry, 2023)
Background: This study aimed to examine if there is a connection between recombinant FSH dose and OS parameters in serum and the impact on IVF outcome. Methods: This study consisted of 101 participants that went through IVF procedures. Parameter that were tested are SOD, SH groups and MDA.  Serum samples were drawn before stimulation and on the last day of ovarian stimulation. Results: Two groups were formed according to the dose of gonadotropins (rFSH). In both groups there were no significant differences in live–birth rate and miscarriage. In both groups mean serum MDA and SH-groups were significantly higher after ovarian stimulation, but mean serum SOD was significantly lower when compared to values before stimulation. There were less patients without OS before stimulation.Conclusion: Our results suggest that there is a difference in serum concentration in groups SOD, SH groups and MDA at the beginning and at the end ovarian stimulation. On the other hand, dose of rFSH is not related with change of parameters for oxidative stress, quality of oocytes, embryos, fertilization, pregnancies, and miscarriage rate. Patients without oxidative stress before the IVF procedure needed lower doses of gonadotropins during stimulation.Keywords: in vitro fertilization, oxidative stress, gonadotropin dose